Protocol of dental biofilm control employed by the discipline of primary healthcare at the Federal University of Ceara, Brazil - Luiza Maria Dias FIRMEZA; Eugenira Ferreira SILVA; Maria Renir CAMPOS; Antônio Sergio LUZ E SILVA; Walda Viana Brígido de MOURA; Ana Karine Macedo TEIXEIRA (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: The objective of the study was to investigate the effectiveness of a protocol of dental biofilm control designed based on an active learning strategy. Methods: A cross-sectional study was carried out with secondary data. The sample consisted of 42 patient records. Information about the patient´s knowledge, perception of oral health, and motor coordination was collected before and after the implementation of the protocol. The plaque index was used to evaluate the oral hygiene level of the patients. Results: At the first evaluation, the results of knowledge and perception were better than the ones of motor coordination. It was also observed a significant increase in the satisfactory percentages for the use of toothbrush and dental floss when comparing the first to the final evaluation. Moreover, there was a significant decrease in the plaque index through the appointments. There were no significant differences in the decrease of plaque index when comparing different genders and ages. However, there was a greater increase of satisfactory scores regarding oral health habits among men and younger age group. Conclusions: There was a significant reduction in the plaque index and an increase in the adoption of satisfactory health habits through the appointments. Although the decrease in plaque index was significant, it was still high, suggesting the need for a higher number of follow-up appointments to reinforce oral health habits.